(untitled) (Experimental biology, 2016)
The paper presents the application of haploid technology in glutinouse rice breeding. As a result of years of research in IPBB, Kazakhstan first obtained dihaploid rice and field tested in the rice-growing regions of the country. For obtaining doubled haploids of rice 24 hybrids, 2 lines and 9 varieties of domestic and foreign rice breeding were used. Anthers were cultured on N6 medium containing 2 mg / l 2,4 D and 90 g / l maltose. As a result of study, perspective aligned doubled haploid lines were created and their field test was carried out under the Almaty region. The structural analysis of economically-valuable attributes analogues and doubled haploids rice were grown in the field. Screening for the amylose content of genotypes was showed low amylose content (from 1.86 to 3.17%) representant interest for glutinous breeding rice. It was identified doubled haploids F1 GS-207, F1BR-4 with high initial growth under 0.75% chloride salinity.